Recent and Noteworthy Legal Works Published in China - Sidel, Mark (Columbia Journal of Asian Law, 1987)
1985 and 1986 were banner years in Chinese legal publishing. More than ever, Chinese legal scholars and commentators were freed from producing numbingly repetitive law textbooks and guides for cit- izens on such topics as family law and criminal law and began to write books and articles, some imbued with an unprecedented innovative spirit, on subjects as varied as administrative law, inheritance law, bankruptcy, intellectual property and the relationship between law and democracy. Works examining the traditional subjects of the Chi- nese legal scholar and commentator, economic law, criminal law and procedure, civil law, family law and legal history, are now more lively and imaginative and often employ specific case examples. Books of civil and criminal cases, a new genre in Chinese legal publishing, have burst upon the stage. Academic and popular law journals have emerged relatively free of restraint, while such established journals as the scholarly Faxue Yanjiu (Studies in Law) and the popular Minzhu yu Fazhi (Democracy and the Legal System) have improved considerably. China’s national law newspaper, Zhongguo Fazhibao (Chinese Legal Gazette) published six times weekly, now claims a circulation of over 1.9 million copies and many times that number of actual readers. The Chinese Legal Gazette is complemented by over two dozen local fazhibao (legal gazettes or newspapers) published from Tibet to Beijing and from Xinjiang to Guiyang and Harbin. Numerous other legal periodicals are discussed below.